President Trump Announces U.S. Troop Withdrawal from Syria. Issue 2 (9th April 2019) - Unknown
Abstract : Begun over seven years ago, the conflict in Syria became and remains a humanitarian crisis. The United States entered the conflict in 2014 and has since been involved through its use of airstrikes and deployment of ground forces. On December 19, 2018, President Trump announced his decision to withdraw U.S. troops from Syria. In the months subsequent to this announcement, unsettled questions have lingered regarding a timeline for withdrawal, the fate of the U.S.-backed Kurdish forces in Syria, and how the decision to withdraw will affect U.S. interactions with other Middle Eastern countries.